Peran Dan Etika Tanggung Jawab Sosial Dalam Bisnis Internasional - Nabila Rizki Erjani (Jurnal Publikasi Ilmu Manajemen, 2024)
The emergence of international business is because no single country can afford all the needs of its country, both in terms of goods and services, so that international trade arises as a result of the interaction between competitive demand and supply. International business provides changes and new colors in the business world. Social responsibility in international business has a very big role, because the company's main goal, apart from making a profit, is to attract interest. This research uses a qualitative approach, namely describing and explaining the role of ethics and social responsibility in international business.